Analysis of Reaction Kinetics of Edible Oil Oxidation at Ambient Temperature by FTIR Spectroscopy. Issue 6 (19th May 2020) - Wang, Mengzhu; Chen, Jia; Jing, Bingyu; Zhang, Lingyan; Dong, Yaoyao; Yu, Xiuzhu
Abstract: Edible oils are studied to analyze their reaction kinetics during oxidation and predict shelf life at ambient temperature. Rapeseed oil (RO), soybean oil (SO), linseed oil (LO), and peanut oil (PO) are detected via Fourier transform infrared spectroscopy with a mesh cell as spectral acquisition accessory. The reaction kinetics of ROOH bonds, C═O bonds, trans double bonds (TDBs), and carbon chain skeletons (CCSs) are determined by absorbance changes in their characteristic absorption peaks. Prediction models for shelf life based on various characteristic absorption peaks are converted via the reaction kinetics equations of the oils. Results show that first‐order reaction kinetics are used to describe absorbance changes of ROOH bonds in PO, SO, and LO, while zero‐order reaction kinetics are used to describe the absorbance changes in RO. Both C═O bonds and CCS absorbance changes in the four oils satisfy first‐order reaction kinetics. TDBs absorbance changes in PO, SO, and LO are in accordance with zero‐order reaction kinetics. The regression equations of reaction kinetics exhibit good fitting degree (coefficient of determination, R 2  > 0.9000) and statistical significance ( p  < 0.001), indicating that the proposed method can be used to analyze the reaction kinetics of oil oxidation and predict shelf life. Practical Applications : The reaction kinetics of RO, SO, LO, and PO are studied at ambient temperature and the shelf life is predicted by using FTIR spectroscopy based on the absorbance changes of ROOH bonds, C═O bonds, TDB bonds, and CCS in the oils. The shelf life of edible oils can be more effectively predicted in this case and provide a practical reference for food industries. Furthermore, the proposed technique is rapid, green, and accurate, and allows real‐time characterization of absorbance changes in various characteristic absorption peaks, which corresponded to different oxidation products. By this method, it is possible to reflect real‐time information for different quality indices (such as peroxides and acid values) of oil oxidation simultaneously, and unnecessary to measure these indices directly one by one, saving manpower and material resources. Therefore, FTIR spectroscopy is convenient for the rapid evaluation of oxidation stability and shelf life of edible oils under ambient temperature. Abstract : The reaction kinetics of rapeseed oil, soybean oil, linseed oil, and peanut oil are studied at ambient temperature based on the absorbance changes of ROOH bonds, C═O bonds, trans double bonds, and carbon chain skeletons. Prediction models for shelf life based on various characteristic absorption peaks are converted via the reaction kinetics equations of the oils.